DISCUSSION TERRACE ANEMIA PREVENTION IN FEMALE ADOLESCENTS BY UNDERSTANDING THE CAUSES AND SOLUTIONS - Ni Ketut Alit Armini; Esti Yunitasari; Mira Triharini; Margareta Nendy; ,Jessica Berliana Berliana; Ushaq Legenda; Alifia Zuqni Tajrida; Dita Dwi Oktav; Nur Afifah (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2022)
Introduction: Female adolescents are a group that is prone to anemia due to puberty, experiencing menstruation, and an inappropriate diet. Community service activities aim to increase the understanding of young women about anemia to be able to make prevention efforts. Methods: Community service activities are carried out through webinars with a zoom platform. Activities include lectures, and interactive discussions, interspersed with fun games. A total of 32 teenagers participated in the activity until the end. The media used during the activity was in the form of presentation slides. Evaluation is done by asking open-ended questions and the opportunity to provide feedback to the participants. Results: Teenagers enthusiastically participated in the webinar on anemia discussion. Adolescents can mention the meaning, causes, signs and symptoms, and efforts to overcome anemia. Teenagers are interested in consuming COO-BIT! which is introduced. Conclusion: The teenagers understand anemia prevention and are committed to paying attention to healthy nutritional intake after participating in the discussion terrace. Teenagers are motivated to take care of their health. Keywords: Adolescent; anemia; behavior; gender equality; prevention